PRINCIPLES OF RESPONSIBILITY OF BUSINESSES FOR THE ADDITION OF EXONERATION CLAUSULES IN ELECTRONIC TRANSACTIONS THROUGH INTERNET WEBSITES REVIEWED FROM THE LEGAL PERSPECTIVE OF CONSUMER PROTECTION - Bisma (Awang Long Law Review, 2021)
In this study the focus on exoneration clauses in online / online site electronic transactions can place an unbalanced position between businesses and consumers. Business actors freely include exoneration clauses in online / online sites for the purpose of legal protection for the business actors themselves. Thus, this dissertation research is research on "Principles of Business Responsibility for Inclusion of Exoneration Clauses in Electronic Transactions Through Internet Sites Judging from the Perspective of Consumer Protection Law. The results of his research are firstly, the position of the exoneration clause in business transactions through internet sites (online) in Indonesian law is located in the field of civil law as part of the contract law, so that Article 1320 of the Civil Code applies to the legal conditions of an agreement. Second, the form of responsibility of business actors to consumers in business transactions through internet sites (online) to gain access to responsibilities adapted by Law Number 8 of 1999 concerning Consumer Protection by giving compulsory business actors to pay compensation for defective products. Article 19 paragraph (1) UUPK. Thus, the UUPK allows consumers to submit a claim to business actors to take responsibility for the losses they suffer. Third, the ideal arrangement related to business transactions through internet sites that provide more sense of protection for consumers. based on research, in Indonesia there are many settings specifically for electronic transactions. Related regulations can be found by interpreting these regulations into an understanding of electronic transactions or linking one rule to another. the form of responsibility of business actors to consumers in business transactions through internet sites (online) to gain access to responsibilities adapted by Law Number 8 of 1999 concerning Consumer Protection by giving compulsory business actors to pay compensation for defective products. Article 19 paragraph (1) UUPK. Thus, the UUPK allows consumers to submit a claim to business actors to take responsibility for the losses they suffer. Third, the ideal arrangement related to business transactions through internet sites that provide more sense of protection for consumers. based on research, in Indonesia there are many settings specifically for electronic transactions. Related regulations can be found by interpreting these regulations into an understanding of electronic transactions or linking one rule to another. the form of responsibility of business actors to consumers in business transactions through internet sites (online) to gain access to responsibilities adapted by Law Number 8 of 1999 concerning Consumer Protection by giving compulsory business actors to pay compensation for defective products. Article 19 paragraph (1) UUPK. Thus, the UUPK allows consumers to submit a claim to business actors to take responsibility for the losses they suffer. Third, the ideal arrangement related to business transactions through internet sites that provide more sense of protection for consumers. based on research, in Indonesia there are many settings specifically for electronic transactions. Related regulations can be found by interpreting these regulations into an understanding of electronic transactions or linking one rule to another.